Uluslararası Anlaşmaların Filistin Hukukundaki Yeri - Mahmoudhamad, Yousef M. A. (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
Birleşmiş Milletler Genel Kurulu Kasım 2012 sonunda Filistin'i Birleşmiş Milletlere üye olmayan gözlemci devlet olarak kabul etme kararının ardından, Filistin resmi makamları çok sayıda uluslararası çok taraflı antlaşmaya katılım belgelerini sunmaya başladı. Bu süreç, Filistin Devleti’nin ulusal geleceğini şekillendirmede etkin bir katılımı garanti eden bir siyasi ve hukuki sistem inşa etmeyi amaçladığını göstermektedir. 2018 yılının sonuna kadar yapılan tahminlere göre, Filistin Devleti'nin taraf olduğu uluslararası antlaşmaların sayısı yaklaşık yüz civarındadır. Filistin Devleti birçok uluslararası antlaşmaya taraf olmasına rağmen, Filistin Temel Kanunu (Filistin Anayasası), uluslararası anlaşmalarla ilgili bazı konuları düzenlememiştir. Mesela, uluslararası antlaşmaların Filistin hukuk sistemindeki yeri ve onları onaylamaya yetkili makam konularında düzenlemelere rastlamamaktayız. Buna ek olarak, bu uluslararası antlaşmaların yürürlüğe girmesi, sonrasında ise uygulanması konusunda bir takım hukuki ve pratik sorunlar ortaya çıkmaktadır. Bu durum, bu anlaşmaların ne şekilde ele alınacağı ve etkin bir şekilde uygulanmasının sağlanması için hangi mekanizmaların uygun olduğu konusunda soru işaretleri yaratmıştır. Bu bağlamda, bu çalışma, söz konusu sorunları ve bunların iç hukuk sistemine etkilerini açıklamayı, gerekli çözümleri bulmayı ve Filistin Devleti’nin uluslararası yükümlülüklerini yerine getirme kapasitesini artırmayı hedeflemektedir.

At the end of November 2012, the United Nations General Assembly passed a resolution recognizing the State of Palestine as an observer state. After that, Palestinian officials began submitting applications to accede to many multilateral international treaties, looking to build a political and legal system that guarantees its effective participation as an active member of the international community. As of the end of 2018, the number of treaties to which the State of Palestine has acceded has reached more than 100 multilateral international conventions and treaties. Although the State of Palestine has acceded to multiple international treaties and has imposed international obligations on itself in multiple fields, the Palestinian Basic Law (the Constitution of Palestine) has not specified a number of issues related to international treaties, whether those related to determining the status of international treaties in the Palestinian legal system or determining what is competent authority to ratify them. In addition, a number of legal and practical issues have arisen in the application and enforcement of these international agreements in domestic law, raising questions about how to deal with these agreements and what are the appropriate mechanisms to ensure their effective implementation. In this context, this study attempts to clarify these issues and their impact on the domestic legal system, find the necessary solutions and provide practical recommendations that would enhance the State of Palestine's ability to fulfill its international obligations and achieve greater benefit from its status as an observer state on its way to obtaining full membership as an independent state and an integral part of the international community.
The Postion of International Treaties in The Palestinian Legal System
Keywords: Uluslararası Anlaşmalar; İç Hukuk; Uluslararası Hukuk; Filistin Hukuk Sistemi; Filistin Antlaşmaları; Filistin Temel Kanunu; Filistin Yüksek Anayasa Mahkemesi; International Treaties; Internal Law; International Law; Palestinian Legal System; Palestinian Agreements; Settlement of Treaties; Palestinian Basic Law; The Palestinian Supreme Constitutional Court